The Effect of Motivation and Employee Well-Being on Employee Retention at the Cirebon Branch of BULOG - Honneyfah Nurrahmat; Agi Syarif Hidayat (Universitas KH. Abdul Chalim Mojokerto, 2026)
Employee retention has become a critical issue in public sector organizations due to increasing workforce mobility and organizational restructuring, making it important to understand key factors that influence employees’ wilingness to continue working within an organization. This study investigates the impact of motivation and employee well-being on employee retention at Perum BULOG Cirebon Branch. A quantitative research method with a causal associative design was applied, involving all 66 employees as respondents using a saturated sampling technique. Data were obtained using structured questionnaires and subsequently analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS software. The findings demonstrate that the measurement model satisfies the requirement of convergent validity, discriminant validity, and reliability, as indicated by acceptable outer loading values, Average Variance Extracted (AVE), Cronbach’s alpha, and composite reliability exceeding the recommended thresholds. Structural model analysis reveals that motivation and employee well-being simultaneously explain 50.5% of the variance in employee retention and demonstrate adequate predictive relevance. Hypothesis testing shows that motivation exerts a positive and significant influence on employee retention, while employee well-being also has a positive and significant effect with a stronger influence. These findings confirm that both motivation and employee well-being are essential determinants in strengthening employee retention within public sector organizations.